CHINESE COMMUNITY LANGUAGE MAINTENANCE: PERCEPTIONS OF AND EFFORTS MADE BY YOUNG MALAYSIANS IN PENANG - Ong, Teresa Wai See (Sanata Dharma University, Yogyakarta, 2025)
In the present era, minority/less dominant languages are spoken lesser and lesser due to language shift that is taking place. This situation is worrying because these languages are facing endangerment. Hence, it urges for a call to examine people’s perceptions of speaking them and efforts to maintain them. Using the Chinese community in Penang, Malaysia as a case study, this study investigates the stated issues. Data collection took place in 2016 with 22 young Malaysians aged 20-40 years old. A semi-structured interview was conducted with the participants and the transcripts were analysed using thematic analysis. The findings reveal that the participants are keen about the continuation of speaking Chinese community languages due to three main reasons: (i) Chinese community languages are a representation of history and family roots, (ii) speaking to them represents possessing multiple identities and (iii) they act as a living culture. They reported that many efforts were made to maintain the continuous usage of Chinese community languages. This study concludes that youth need to be engaged with those efforts to ensure that the Chinese community languages do not disappear in the future. This can be done by including the use of digital technology in those efforts.